Herbal Usage History as a Risk Factor for Delay in Treatment on Breast Cancer Patients in Surakarta - Niluh Ayu Anissa Hanum; Kristanto Yuli Yarso; Riza Novierta Pesik (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Breast cancer is a most commonly diagnosed cancer in women with an estimated 1.67 million cases diagnosed in 2012, i.e. 25% of all cancer cases. As many as 69% of breast cancer incidence was found to have reached stage III and IV, which has lower five-years survival rate. Various factors play a role in the delay of treatment, one of them is an herbal usage history. This study aims to determine whether an herbal usage history is a risk factor of delay in breast cancer patients in Surakarta. Methods: This study design was observational analytic with cross sectional approach. The samples were 45 breast cancer patients with delayed treatment and 55 breast cancer patients without delay treatment in RSUD Dr. Moewardi and RSU Kasih Ibu Surakarta. Samples were taken by fixed disease sampling, which then selected based on inclusion and exclusion criteria. The instrument used is the patient records and supplementary questionnaire. The variables studied were delays in treatment with an herbal usage history along with other confounding factors that may affect the delay of treatment. Data then analyzed using bivariate test and logistic regression. Results: The results of the bivariate analysis showed that an herbal usage history is a risk factor of delay in treatment, with p = 0.002 and OR = 3.69. While the results of the multivariate analysis showed that a low level of knowledge affect the most to delays in treatment of breast cancer with OR = 3.699. Conclusions:Herbal usage history was proved as a risk factor for delay in treatment on breast cancer patients in Surakarta. Keywords:Herbal Usage History, Delay in Treatment, Breast Cancer